2016
DOI: 10.21106/ijma.66
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Interventions to Reduce Maternal Mortality among HIV-Infected Pregnant and Postpartum Women

Abstract: Background:In high-prevalence populations, HIV-related maternal mortality is high with increased mortality found among HIV-infected pregnant and postpartum women compared to their uninfected peers. The scale-up of HIV-related treatment options and broader reach of programming for HIV-infected pregnant and postpartum women is likely to have decreased maternal mortality. This systematic review synthesized evidence on interventions that have directly reduced mortality among this population.Methods:Studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In our study, the majority of HIV‐infected women were diagnosed during pregnancy and this points to a need to increase routine HIV testing outside of pregnancy to allow linkage to care and early initiation of ART. Preconception ART is associated with a decreased risk of HIV‐related maternal deaths .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the majority of HIV‐infected women were diagnosed during pregnancy and this points to a need to increase routine HIV testing outside of pregnancy to allow linkage to care and early initiation of ART. Preconception ART is associated with a decreased risk of HIV‐related maternal deaths .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of interventions to improve postpartum retention in HIV care are limited. The majority of this research has been conducted in low-resource or moderate-resource countries and often addresses uptake and adherence to perinatal prevention interventions in addition to postpartum retention in care [ 5 , 6 ]. In a recent review of these topics in relation to pregnant and postpartum women initiating antiretroviral therapy (ART) in sub-Saharan Africa, Myer et al [ 4 ] examine key issues related to adherence and retention and emphasize the need for additional understanding and innovative interventions.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 Cochrane systematic review of maternal and newborn health outcomes after VAS in pregnancy concluded that in pregnant women living with HIV, antenatal VAS reduces the risk of maternal anemia and night blindness ( 99 ). Two RCTs highlighted in another systematic review ( 193 ) provided antenatal VAS to pregnant women living with HIV, and found that VA either had no significant protective effect against maternal mortality ( 194 ) or reduced the benefits observed when added to a multivitamin regimen ( 195 ).…”
Section: Resultsmentioning
confidence: 99%